Is Chinese business education ready for the era of services economy? – A survey into Chinese services management education. (1st January 2011) - Tian, Hui; Berg, Daniel
As the focus of the Chinese economy changes from manufacturing to services, Chinese business education and research need to be refocused. This paper addresses several issues related to services management (SM) education in Chinese business schools. A questionnaire survey with 246 faculty members from 50 top Chinese business schools was conducted to explore how SM education is being carried out in China. The issues in question are: the importance of SM, the degree of attention to SM, the current situation and trend of collaboration in SM between business schools and industry, the status quo and the potential of SM course development. The survey shows a mixed result: on the positive side, SM has been developing into a legitimised course and spread across 24 sample business schools of Chinese key national universities since 1990s; on the negative side, there are still quite a few constraints in SM research and education in Chinese business schools. Based on the data results, some suggestions are made on SM education. The implications of this report, its limitation and future research directions are also discussed.